2021
DOI: 10.3390/biomedicines9040352
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nanosheet-Coated TiZrPdSiNb Alloy as a Piezoelectric Hybrid Material for Self-Stimulating Orthopedic Implants

Abstract: A Ti-based alloy (Ti45Zr15Pd30Si5Nb5) with already proven excellent mechanical and biocompatibility features has been coated with piezoelectric zinc oxide (ZnO) to induce the electrical self-stimulation of cells. ZnO was grown onto the pristine alloy in two different morphologies: a flat dense film and an array of nanosheets. The effect of the combined material on osteoblasts (electrically stimulable cells) was analyzed in terms of proliferation, cell adhesion, expression of differentiation markers and inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Careta et al . found that a ZnO-NP coating on the surface of Ti alloy is non-cytotoxic and could promote the expression of early differentiation genes of osteoblasts without external stimulation [ 32 ]. Therefore, we should verify the cytotoxicity of synthesized hydrogels in further investigations and select a compound hydrogel with better antibacterial performance and no cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Careta et al . found that a ZnO-NP coating on the surface of Ti alloy is non-cytotoxic and could promote the expression of early differentiation genes of osteoblasts without external stimulation [ 32 ]. Therefore, we should verify the cytotoxicity of synthesized hydrogels in further investigations and select a compound hydrogel with better antibacterial performance and no cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Electrical stimulation of cells has shown great potential in wound healing and tissue repair [ 188 ] through activation of different mechanisms and pathways, resulting in enhanced cell proliferation, migration, and differentiation. Attempts were made in order to take advantage of these effects in a targeted manner; hence the piezoelectric properties of ZnO-based nanomaterials have been employed, creating a self-activating source, inside the tissue, producing electric fields through non-invasive and selective means [ 189 , 190 ].…”
Section: Biological Applications Of Nanostructured Znomentioning
confidence: 99%
“…105,106 Among them, ZnO is a typical piezoelectric inorganic material, usually with extremely high piezoelectric coefficient and good mechanical properties, showing excellent application potential in the field of electroactive tissue repair. 107 Based on this, related researchers have prepared a series of therapeutic platforms endowed with mechanical response functions based on ZnO NPs, comprising tissue engineering scaffolds, 108,109 composite material coatings, 110 piezoelectric dermal patches, 111 etc. Their effects on angiogenesis, wound healing and bone tissue formation were also explored.…”
Section: Mechanical Force-triggered Therapymentioning
confidence: 99%
“…On this basis, researchers modified a ZnO nanosheet coating on the surface of a Ti-based alloy (Ti 45 Zr 15 Pd 30 Si 5 Nb 5 ) to induce electrical self-stimulation of osteoblasts, while avoiding the use of silicon. 110 Besides, in terms of nerve repair, Zheng et al 113 loaded ZnO into polycaprolactone (PCL), a commonly used material for nerve conduit manufacturing, and fabricated ZnO/PCL piezoelectric nanogenerator scaffolds by means of 3D injectable multilayer biofabrication technology. Subsequently, the effect of the ZnO/ PCL scaffold on the viability of Schwann cells was investigated, which suggested that the ZnO/PCL scaffold had low toxicity similar to the PCL scaffold (Fig.…”
Section: Mechanical Force-triggered Therapymentioning
confidence: 99%